Toward sustainable additive manufacturing of PEKK/Martian regolith composite for lightweight structural applications on Mars - Farshad Malekpour; Marjan Abdali; Mehdi Hojjati; Krzysztof Skonieczny (Additive Manufacturing Letters)
Advances in sustainable resource utilization and innovative manufacturing techniques are driving efforts toward the prospect of human settlement on Mars, led by programs such as SpaceX’s Occupy Mars initiative. One promising approach involves the development of materials and processes that leverage in-situ Martian resources. In this study, we investigate the fabrication and characterization of a composite material consisting of Polyether-Ketone-Ketone (PEKK) incorporated with Martian Regolith Simulant (MRS), targeting sustainable applications in outer space. Amorphous PEKK was pulverized and mixed with sieved MRS particles, followed by extrusion through a twin-screw extruder to produce a filament with a consistent diameter suitable for Material Extrusion Additive Manufacturing (MEAM). A post-processing protocol, including annealing, was implemented to optimize the degree of crystallinity and improve mechanical properties. The filament quality and dispersion of regolith within the matrix were evaluated, and the composite was characterized through mechanical and thermomechanical analyses. Based on the material properties achieved, a conceptual Mars rover wheel featuring a lightweight graded structure was designed and successfully fabricated. These results demonstrate the early-stage feasibility of producing high-quality, mechanically robust 3D-printed components from regolith-based composites, highlighting the potential of integrating additive manufacturing with local resources as a step toward sustainable extraterrestrial exploration.